Austerity, policy and sport participation in England. Issue 1 (2nd January 2018) - Widdop, Paul; King, Neil; Parnell, Daniel; Cutts, David; Millward, Peter
ABSTRACT: This study seeks to understand participation levels in sport across socio-demographic groups, specifically for the period 2008–14, in the context of austerity measures taken by central government resulting in local authority income and expenditure reductions. Participation levels over time were analysed using data from the Active People Survey (APS), which was the preferred method for measuring participation by Sport England until its replacement in 2015. Budgetary constraints in local authorities have subsequently resulted in an expenditure decrease for non-discretionary services including 'sport development and community recreation'. This area of expenditure forms one component of sport-related services and primarily focuses on raising participation in 'hard-to-reach' groups. The study found that policy goals associated with raising and widening participation were not met to any significant degree between 2008 and 2014 as participation levels have changed little for lower income 'hard-to-reach' groups. It is claimed that this outcome is in part due to austerity measures impacting on local authority expenditure. This study has implications for policymakers and practitioners as it illustrates both the challenges faced in setting and delivering policy aimed at raising participation levels in 'hard-to-reach' groups, particularly in the context of austerity, and the difficulties associated with measuring participation.